An experimental and numerical investigation of heat transfer effect on cyclic fatigue of gas turbine blade (Journal of Engineering, 2019)
Blades of gas turbine are usually suffered from high thermal cyclic load which leads to crack initiated and then crack growth and finally failure. The high thermal cyclic load is usually coming from high temperature, high pressure, start-up, shut-down and load change. An experimental and numerical analysis was carried out on the real blade and model of blade to simulate the real condition in gas turbine. The pressure, temperature distribution, stress intensity factor and the thermal stress in model of blade have been investigated numerically using ANSYS V.17 software. The experimental works were carried out using a particular designed and manufactured rig to simulate the real condition that blade suffers from. A new controlled method in this rig was suggested to heating the specimen depending on Oxygen-gas flame. The numerical result shows that the temperature distribution over the blade varying with the load change, which leads to increase the stress intensity factor along the crack. The experimental result indicates that the rate of crack propagation varying with the position of crack and with the angle of inclined. Based on this result, more effective cracks on the blade were satisfied which are highly effect the blade lifetime.